(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
This paper reflects on the features of current fonts created for persons with dyslexia. First, it addresses the explanation of reading, as an affected ability in the persons with dyslexia, then it suggests a description of dyslexia as the most common learning difficulty and points out the key theories for its origin, as well as the basic deficits that occur in these persons and put a strain on the reading process. This interpretation of the basic terminology is followed by a comparative analysis of the researches related to the fonts for dyslexia, as an introduction to the essential features of these fonts. The font features are explained in the third part of the paper. In it, general features of fonts are clarified, and afterwards it is stated how these features vary in the fonts for dyslexic readers, in order for them to be adjusted to their needs. Though a comparison between the best known Latin fonts is made, there is a description of a font created with the same purpose, but for the Cyrillic script.